Antidiabetic Activity of Ethanol-Water Fraction of Longjack Root (Eurycoma longifolia Jack.) in Streptozotocin-Nicotinamide Induced Rats - Wiwik Hartika; Michelle Terrence; Ikhsan Samir; Ruqiah Ganda Putri Panjaitan (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the decrease in glucose levels, MDA levels, and histopathological appearance of the pancreatic organs of Wistar white rats after administration of the ethanol-water fraction of longjack root. This study used a completely randomized design with four treatment groups and six replications. The treatment consisted of normal control, negative control (Na-CMC 0.5% 5 ml/200 g body weight), positive control (glibenclamide 0.09 mg/200 g body weight), and treatment of the ethanol-water fraction of longjack root with a dose of 500 mg/kg body weight. The results showed that the ethanol-water fraction of longjack root at a dose of 500 mg/kg body weight had antidiabetic activity comparable to that of glibenclamide at a dose of 0.09/200 g body weight, namely blood glucose levels and MDA levels in white rats of 123.55 mg/dl and 2.83 nmol/ml. The results of histopathological analysis of the pancreas of white rats showed that administration of the ethanol-water fraction of longjack root could repair damage to the islets of Langerhans due to the administration of streptozotocin-nicotinamide.